Measuring Verbal Psychotherapeutic Techniques—A Systematic Review of Intervention Characteristics and Measures - Gumz, Antje; Treese, Barbara; Marx, Christopher; Strauss, Bernhard; Wendt, Hanna (Frontiers in Psychology, 2015)
Language is one of the most important “tools” of psychotherapists. The working mechanisms of verbal therapeutic techniques, however, are still marginally understood. In part, this is due to the lack of a generally acknowledged typology as well as a gold standard for the assess-ment of verbal techniques, which limits the possibility of conducting studies focusing this topic. The present study reviews measures used in clinical research which assess directly ob-servable dimensions of verbal interventions in a reliable manner. All measures were evaluated with respect to their theoretical foundation, research goals, assessment modes, and various psychometric properties. A systematic search in databases (PubMed, PsycInfo, PsycArticles, PSYNDEX, Web of Science, Embase) followed by an additional “snowballing” search cover-ing the years 1940-2013 yielded n=179 publications eligible for review. Within these publica-tions, 34 measures were identified showing great heterogeneity regarding the aspects under study. Only two measures reached the highest psychometric standards and can be recom-mended for clinical use without any reservation. Central problems include deficiencies in the systematization of techniques as well as their partly ambiguous and inconsistent definitions. To promote this field of research, it will be important to achieve a consensus concerning the terminology, conceptions and measures of verbal techniques.